Older adults shielding at home - Ward, Mark; Kenny, Rose (TILDA, 2020)
Two thirds of adults aged 60 and older agreed or strongly agreed with shielding. Interestingly, a higher percentage of those most affected by policy, the over 70s, agreed with it. Whether people lived alone or with others does not appear to influence their level of agreement with shielding. On average, those who agreed or agreed strongly with shielding were more concerned about the virus. These findings suggest widespread support for the governments’ decision to ask the over 70s to remain at home and limit their interactions for long periods of time. The level of agreement with shielding was also related to the ease with which older adults understood government guidance on the pandemic. This clearly illustrates the importance of clear communication of these policies and suggests that older adults are willing to adhere to guidelines when they understand the reasoning behind them. Future TILDA research will enable to ascertain whether this agreement was consistent during the entire period the restrictions were in place or if they changes over the course of the pandemic.
PUBLISHED
Dublin
Keywords: Ageing; TILDA; Policy; Shielding; Ageing